Identification of Species of Bambusa by Electrophoretic Pattern of Peroxidases - Kumari, Lalita; Reddy, P. R.; Jagdish, C. A. (Indian Forester, 1985)
Bamboo taxonomists had to resort to criteria, other than floral characters, due to their highly erratic flowering, posing problems for their classification and identification. Presently an attempt has been made to identify thirteen species of Bambusa basing on electrophoretic resolution of peroxidase isozymes. These have been used successfully in the past for species and cultivar identification of several crop plants. Basing our conclusions on the relative mobility and density of different bands, identifying features of these 13 species are presented in the form of a key. Further basing on the same characters 6 species namely B. nutans, B. glaucescens, B. polymorpha, B. arundinacea, B. longispiculata, B. tulda, are brought together in one group and four species namely B. vulgaris, B. ventricosa, B. pallida, B. balcooa in another group. B. burmanica, B. copelandil, B. oliveriana did not show many resemblances with either of the groups.